2001
DOI: 10.1143/jjap.40.1647
|View full text |Cite
|
Sign up to set email alerts
|

Mask Films for Thermally Induced Superresolution Readout in Rewritable Phase-Change Optical Disks

Abstract: Tellurium was studied as a mask film in a thermally induced superresolution rewritable optical disk for detecting below-diffraction-limit marks. Mark trains of 0.15 µm could be retrieved with 9 dB in carrier-to-noise (CNR) using an optical system with the laser wavelength of 780 nm and an objective lens of 0.55 numerical aperture. Readout cyclability was examined and methods to further improve readout cyclability were proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The recording conditions for GST were also identical, however, for the case of Si, the recording process was carried out with a P w of 13 mW, a pulse frequency of 7.5 MHz, and a LV of 3 m / s, which implies a mark length of 200 nm. Lu et al 16 reported a similar drop in CNR for a super-RENS disk fabricated with a Te mask layer. 7 for the GST case and For Si, we also measured the CNR at different LVs.…”
Section: Observations Of the Super-resolution Effect From Disks Wmentioning
confidence: 71%
“…The recording conditions for GST were also identical, however, for the case of Si, the recording process was carried out with a P w of 13 mW, a pulse frequency of 7.5 MHz, and a LV of 3 m / s, which implies a mark length of 200 nm. Lu et al 16 reported a similar drop in CNR for a super-RENS disk fabricated with a Te mask layer. 7 for the GST case and For Si, we also measured the CNR at different LVs.…”
Section: Observations Of the Super-resolution Effect From Disks Wmentioning
confidence: 71%
“…This aperture overcomes the resolution limit of the optics used, and the readout of small marks beyond the limit (for higher recording density) becomes possible. The key to this super-resolution technique is the material used for aperture formation, and various materials, e.g., Ge 2 Sb 2 Te 5 , 1) Te, 2) Co 3 O 4 , 3) ZnO, 4) AlGe, 5) Sb, 6) AgO x , 7) Ag 6:0 In 4:5 Sb 60:8 -Te 28:7 , 8) Sb 3 Te, 9) and Ag 2 Te, 10) have been reported.…”
mentioning
confidence: 99%